PARADIGMA ULAMA DALAM MENENTUKAN KUALITAS HADIS DAN IMPLIKASINYA DALAM KEHIDUPAN UMAT ISLAM - Mujibatun, Siti (Analisis: Jurnal Studi Keislaman, 2014)
THE SCHOLARS PARADIGM IN DETERMINING THE QUALITY OF THE HADITHAND  ITS IMPLICATIONS  FOR THE USE OF THE LEGAL BASIS  IN THE DAILY LIFE OF MUSLIMS TODAY. The emergence of internal conflicts religious (Islam)  in  the  practice  of  religion  in  daily  life  caused  by  the different sects among the hadith scholars since the early Islamic period  to  the  present,  especially in determining  the  quality  of the hadith as evidence syar’iyyah. The scholars of Hadith have a typology and different concepts, so a significant impact on the use of different  reference amaliah  Muslims  today.  Even sometimes cause reactions  mislead each other  and each other  infidel. The article aims to determine the paradigm in determining the quality of the hadith scholars, so as to know the strengths and weaknesses of each school and its implications  for the use of the legal basis in the daily life of Muslims today.The  findings of this study are as follows: a). There are four schools in determining  the quality of the hadith scholars, namely, mutasyaddid (sstrict), muta’annut (excessive),  mutawassit} (moderate)  and mutasahhil (soft- permissive). B). Implications  school differences in the quality of the lives of Muslim tradition  for the school mutasyaddid  (strict) that  the hadith  does not meet  kaedah validity,  can not be used as proof  syar’iyyah.  Likewise,  schools  mutawassit} (moderate), unless  there  is  the  argument   (Qur’an-hadith)   more  powerful as supporters. Muta’annut  and mutasahhil,  the  schools  tend  to use quality  hadith d}a’i>  f especially to the virtue  of charity  and morals.